2014
DOI: 10.1097/mlr.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Is Bigger Always Better? A Nationwide Study of Hip Fracture Unit Volume, 30-Day Mortality, Quality of In-Hospital Care, and Length of Hospital Stay

Abstract: Patients admitted to high-volume hip fracture units had higher mortality rates, received a lower quality of in-hospital care, and had longer length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 24 publications
4
46
0
2
Order By: Relevance
“…10, 1921 It is also worth noting that while the vast majority of studies have demonstrated a morbidity and mortality benefit to patients undergoing surgery at high volume centers, the literature is not universally supportive of this notion. 2123 …”
Section: Discussionmentioning
confidence: 99%
“…10, 1921 It is also worth noting that while the vast majority of studies have demonstrated a morbidity and mortality benefit to patients undergoing surgery at high volume centers, the literature is not universally supportive of this notion. 2123 …”
Section: Discussionmentioning
confidence: 99%
“…[17] Hospital surgical volume is often linked to quality of care and access to resources. [6] We dichotomized hospitals into higher and lower volume categories by comparing their annual volumes in the year of index surgery with the median of average annual volumes among hospitals of the same type (174 surgeries for teaching hospitals, 141 for community large hospitals, 37 for community medium hospitals). [18,19] Admission time was previously linked to access to resources with fewer support services from late Friday to Monday morning.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown an association between a higher volume of hip fracture surgeries and delays, complications and death. 40,41 The studies suggest underprioritization of hip fracture over other surgeries at high-volume sites. 40,41 Hospital occupancy has also been associated with risk of in-hospital death after hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 The studies suggest underprioritization of hip fracture over other surgeries at high-volume sites. 40,41 Hospital occupancy has also been associated with risk of in-hospital death after hip fracture. 31 Future research should explore the association among teaching status, bed capacity, occupancy and volume to better our understanding of outcomes of hip fracture care delivery.…”
Section: Discussionmentioning
confidence: 99%